2021
DOI: 10.1111/jmg.12581
|View full text |Cite
|
Sign up to set email alerts
|

Metapelite from the high‐ to ultrahigh‐pressure terrane of the Eastern Alps (Pohorje Mountains, Slovenia)—New pressure, temperature and time constraints on a polymetamorphic rock

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(53 citation statements)
references
References 118 publications
11
39
3
Order By: Relevance
“…In addition, it is also debated whether all paragneisses from the southeastern Pohorje Mts experienced UHP. Thus, one of our aims is to clarify this situation by studying metasedimentary rocks from the southwestern Pohorje Mts in addition to the micaschist reported by Li et al (2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is also debated whether all paragneisses from the southeastern Pohorje Mts experienced UHP. Thus, one of our aims is to clarify this situation by studying metasedimentary rocks from the southwestern Pohorje Mts in addition to the micaschist reported by Li et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…In order to address the above problems, we continue our previous work on metasediments (subsequently called micaschists) from the southeastern Pohorje area (Li et al, 2021). During our study, we not only confirmed Eo‐Alpine HP conditions (hereafter termed Stage I) for micaschist obtained by our previous work (Li et al, 2021) but also we detected for the first‐time evidence for a reheating event (hereafter termed Stage III) caused by the Miocene Pohorje pluton in micaschist. Furthermore, we discuss the previously recognized imprint of an Eocene metamorphic event (hereafter termed Stage II) (Li et al, 2021), which we relate to intracontinental subduction.…”
Section: Introductionmentioning
confidence: 99%
“…This implication is strengthened by Spear (2017) who argued for kinetic factors (energetic barriers) being responsible for a significant overstepping of the P-T limit of garnet. Examples for this phenomenon in higher grade metasediments leading to nearly chemically homogeneous porphyroblastic garnet were recently presented by Li et al (2021Li et al ( , 2020. Indeed, the common garnet core in gneiss SWE3-2c is relatively chemically homogeneous.…”
Section: Discussion 61 Pressure-temperature Evolutionmentioning
confidence: 92%
“…In the Prijakt Subgroup of the BSTW, with a similar P-T path, this age classification was not free of doubt, as a distinct population of Carboniferous monazite exists there. However, a Permian metamorphism at an intermediate P-T regime has been reported from regions adjacent to the Saualpe [82][83][84]. It should have preceded a Permo-Triassic low pressure stage with the intrusion of pegmatites.…”
Section: Discussionmentioning
confidence: 99%